Discovering positionalities in the countryside: methodological reflections on doing fieldwork in South India - Kunze, Isabelle; Padmanabhan, Martina (ERDKUNDE, 2014)
Critical reflection on our positionalities fosters a better understanding of our embodied research experiences. Positionalities undergo transformation throughout the process of data collection and analysis. In this paper, we seek to engage with the question of how our situated, fluid positionalities shape relations and the data collection process in the field. To this end we discuss 1) our positionalities as researchers in the research process; 2) field entry; 3) embodied field performances; 4) marital status; and 5) the relationship between research assistants and researcher. Discussion of these interrelated themes is prefaced by a brief introduction to contemporary work on Indian feminism and gendered geographies.